2017
DOI: 10.1186/s12943-017-0624-9
|View full text |Cite
|
Sign up to set email alerts
|

The epithelial to mesenchymal transition (EMT) and cancer stem cells: implication for treatment resistance in pancreatic cancer

Abstract: The mechanical properties of epithelial to mesenchymal transition (EMT) and a pancreatic cancer subpopulation with stem cell properties have been increasingly recognized as potent modulators of the effective of therapy. In particular, pancreatic cancer stem cells (PCSCs) are functionally important during tumor relapse and therapy resistance. In this review we have surveyed recent advances in the role of EMT and PCSCs in tumor progression, metastasis and treatment resistance, and the mechanisms of integrated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
213
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(220 citation statements)
references
References 132 publications
(133 reference statements)
5
213
0
2
Order By: Relevance
“…These findings indicate that the formation of cisplatin resistance is associated with EMT. Numerous studies have shown that EMT plays an important role in the progression, invasion, metastasis and drug resistance of a variety of cancers including GC . In this study, E‐cadherin expression was down‐regulated and vimentin expression was up‐regulated in GC cells treated with cisplatin, indicating that GC cells treated with cisplatin experienced EMT‐like changes.…”
Section: Discussionmentioning
confidence: 54%
“…These findings indicate that the formation of cisplatin resistance is associated with EMT. Numerous studies have shown that EMT plays an important role in the progression, invasion, metastasis and drug resistance of a variety of cancers including GC . In this study, E‐cadherin expression was down‐regulated and vimentin expression was up‐regulated in GC cells treated with cisplatin, indicating that GC cells treated with cisplatin experienced EMT‐like changes.…”
Section: Discussionmentioning
confidence: 54%
“…M2 macrophages are generally considered to be the phenotype of tumor-associated macrophages (TAMs), [454][455][456] have immunosuppressive and angiogenesis-promoting effects, and are considered to be a tumor-promoting cell type. 456,457 M2 macrophages secrete CCL17 (C-C chemokine ligand 17), CCL22, and CCL24 and have low expression of IL-12 and high expression of IL-10. Cytokines secreted by macrophages affect the proliferation, tumorigenic transformation, or apoptosis of CSCs through various signaling pathways.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%
“…We revealed that resistance of EAC cells toward chemoradiation is mediated via EMT and increased stemness. Previous studies have shown that EMT is a critical regulator for acquiring and maintaining a subset of cells within the tumor, the cancer stem cell population . Indeed, cancer stem cells and cells that have undergone EMT are closely related in molecular and phenotypic characteristics.…”
Section: Discussionmentioning
confidence: 99%